Impact of concomitant injuries on outcomes after traumatic brain injury - Leitgeb, Johannes (Springer-Verlag, 2013)
BACKGROUND: Patients with traumatic brain injury (TBI) frequently have concomitant injuries; we aimed to investigate their impact on outcomes. METHODS: Between February 2002 and April 2010, 17 Austrian centers prospectively enrolled 863 patients with moderate and severe TBI into observational studies. Data on accident, treatment, and outcomes were collected. Patients who survived until intensive care unit (ICU) admission and had survivable TBI were selected, and were assigned to “isolated TBI” or “TBI + injury” groups. Six-month outcomes were classified as “favorable” if Glasgow Outcome Scale (GOS) scores were five or four, and were classified as “unfavorable” if GOS scores were three or less. Univariate statistics (Fisher’s exact test, t test, χ(2)-test) and logistic regression were used to identify factors associated with hospital mortality and unfavorable outcome. RESULTS: Of the 767 patients, 403 (52.5 %) had isolated TBI, 364 (47.5 %) had concomitant injuries. Patients with isolated TBI had higher mean age (53 vs. 44 years, P = 0.001); hospital mortality (30.0 vs. 27.2 %, P = 0.42) and rate of unfavorable outcome (50.4 vs. 41.8 %, P = 0.02) were higher, too. There were no significant mortality differences for factors like age groups, trauma mechanisms, neurologic status, CT findings, or treatment factors. Concomitant injuries were associated with higher mortality (33.3 vs. 12.5 %, P = 0.05) in patients with moderate TBI, and were significantly associated with more ventilation, ICU, and hospitals days. Logistic regression revealed that age, Glasgow Coma Scale score, pupillary reactivity, severity of TBI and CT score were the main factors that influenced outcomes. CONCLUSIONS: Concomitant injuries have a significant effect upon the mortality of patients with moderate TBI. They do not affect the mortality in patients with severe TBI. LEVEL OF EVIDENCE AND STUDY TYPE: Evidence level 2; prospective, observational prognostic study.